2007
DOI: 10.1007/s00232-007-9037-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Force Spectroscopy on Desmoglein 1 Using Atomic Force Microscopy Reveal Multivalent Ca2+-Dependent, Low-Affinity Trans-Interaction

Abstract: Desmoglein 1 is a desmosomal member of the cadherin family expressed in stratified epithelia. Desmoglein 1 is the target adhesion molecule of severe blistering skin diseases such as pemphigus or bullous impetigo. However, despite this enormous pathological relevance, the molecular binding properties of desmoglein 1 are largely unknown. Using atomic force microscopic imaging, we found that desmoglein 1 molecules displayed Ca(2+)-dependent conformational changes of the extracellular domains. By single-molecule f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…Such proteins are out of context and thus cannot form the complex cytoplasmic interactions with other desmosomal proteins in the plaque (62). Nevertheless, homophilic binding by desmosomal cadherins has sometimes been reported from studies with transfected L929 cells and recombinant proteins (40,42,55,56). In contrast, work with transfected HT1080 SL-1 fibrosarcoma cells and mammary epithelial cells, both of which form desmosomes, is more consistent with homophilic adhesion (30,41).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such proteins are out of context and thus cannot form the complex cytoplasmic interactions with other desmosomal proteins in the plaque (62). Nevertheless, homophilic binding by desmosomal cadherins has sometimes been reported from studies with transfected L929 cells and recombinant proteins (40,42,55,56). In contrast, work with transfected HT1080 SL-1 fibrosarcoma cells and mammary epithelial cells, both of which form desmosomes, is more consistent with homophilic adhesion (30,41).…”
Section: Discussionmentioning
confidence: 98%
“…Thus anti-adhesion peptides to both Dsc and Dsg were required to block morphogenesis of mammary epithelial cells (30), and a cell type expressing Dsg but not Dsc could form apparently complete desmosomes (41). Homophilic binding is also indicated by atomic force microscopy with tethered recombinant Dsg1 EC domains (42). Surprisingly, there have been no attempts to determine the mode of desmosomal cadherin binding in desmosome-forming cells.…”
mentioning
confidence: 99%
“…Specifi cally, desmoplakin anchored intermediate fi laments Kouklis et al, 1994;Bornslaeger et al, 1996;Meng et al, 1997); plakophilins, plakoglobin, and desmoplakin bound each other to form a plaque (Chen et Kowalczyk et al, 1997;Bornslaeger et al, 2001), and interactions mediated by plakoglobin and plakophilin linked the plaque-fi lament complex to transmembrane, desmogleins, and desmocollins (Smith & Fuchs, 1998;Chen et al, 2002;Bonne et al, 2003;Hatzfeld et al, 2000;Kami et al, 2009;Troyanovsky et al, 1994a, 1994b, Kowalczyk et al, 1996Witcher et al, 1996;Choi et al, 2009;Mathur et al, 1994;Roh & Stanley, 1995;Kowalczyk et al, 1999;Andl & Stanley, 2001;Bornslaeger et al, 2001;Gaudry et al, 2001). The ability of desmosomal cadherins to establish trans interactions between cells, in turn, accounted for the actual adhesive bond formed between two cells (Waschke et al, 2007;Nie et al, 2011;Chitaev & Troyanovsky, 1997;Aoyama et al, 2009).…”
Section: Assembly : Intradesmosomal Protein Interactionsmentioning
confidence: 99%
“…Chitaev and Troyanovsky (1997), specifi cally, identifi ed DSG2-DSC1 complexes established by proteins extending from adjacent cells in trans and, thus, capable of mediating cell -cell adhesion. Homodimers also formed within the desmoglein and desmocollin subfamilies, with preference going to trans interactions between identical isoforms (e.g., DSC2/DSC2 complexes) (Waschke et al, 2007;Nie et al, 2011). Like classic cadherins, desmosomal cadherins bound and relied upon calcium ions to dimerize (Syed et al, 2002;Posy et al, 2008;Rakshit et al, 2012).…”
Section: Assembly : Intradesmosomal Protein Interactionsmentioning
confidence: 99%
“…Using single-molecule atomic force microscopy (AFM), it has been shown that PV-IgG and AK23 monoclonal antibody directly inhibit Dsg3 homophilic binding under cell-free conditions, suggesting that direct inhibition of Dsg3 binding occurs in PV [ 75 , 76 ]. Direct blocking of Dsg1 binding was not observed by this technique (AFM); however, keratinocyte dissociation and loss of Dsg1-and Dsg3-coated microspheres to cultured keratinocytes were observed when using laser tweezer trapping [ 77 ], indicating that acantholysis may not be solely dependent on direct interference of Dsg1-Dsg1 binding by pemphigus autoantibodies. Recent studies using peptides against the desmoglein adhesive interface as well as tandem peptides (obtained by dimerization of two of the initial peptides) added evidence that direct inhibition contributes to acantholysis when the tandem peptide prevented acantholysis induced by PV-IgG, yet this is not the case when using PF-IgG.…”
Section: Direct Interference Of Desmogleins Trans Interaction By Pempmentioning
confidence: 65%